Abscesses caused by Brucella suis in the peri-renal fat of pigs infected by Stephanurus dentatus - Langenegger, Jerome; Langenegger, Charlotte Hubinger; Cueva, Vicente Elias Cueva (Pesquisa Agropecuaria Brasileira, 2014)
The bacteriological examination of abscesses, localized in the peri-renal fat of 300 hogs severely infected by Stephanurus dentatus, revealed infections by Brucella suis in 35.6%, Corynebacterium pyogenes in 13.6%, Pasteurella multocida in 13.0%, Escherichia coli in 2,6% and Corynebacterium equi in 0.6% of the cases. The findings of Brucella suis and other infections in the kidney region is related to the lesions caused by the parasite. The study shows interesting epizootic aspects regarding stephanuriasis and swine brucellosis. It is also of importance for public health.